Islamic Humanism Education for the World - Sobry, M. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
In this article the author tries to describe Islamic humanism education/humanist education. This conception is an offer against the restlessness and anxiety of Human in the conception of Western education as well as the actual offer of Islam and scholars for education, people, and the world. The conception of Humanist Education is based on the study of Islamic epistemology, namely "revelation". "Revelation" occupies a position as one of the constructors of reality because revelation is recognized as "God’s verses" those are able to provide guidance in one’s thoughts and actions. Social change is an integral part of the conception of Islamic humanist education. The order of human life that is upheld is the creation of justice and equality (egalitarian). Education is actually a struggle to realize that life and order. The order expected by humans in the world today is world peace.